IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PROGRAM SEKOLAH HARMONI HIJAU DI SEKOLAH DASAR NEGERI KOTA SINGKAWANG - Jacobus, Arnold (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research aims to find out the implementation of education character through green harmony school program in the elementary school in terms of planning, realization, and evaluation of learning. This research was conducted at the elementary school 62 Singkawang and the elementary school 94 Singkawang. This research is a qualitative descriptive research. The informants of the research are the head master, teachers, and students. The techniques to collect the data are structured interviews, observations, and document studies. The steps to analyze the data are data reduction, data display, and drawing the conclusion. Data validity tested by triangulation technique and resources. The result showed that the implementations of education character in the planning, realization, and learning evaluation have been done well and correspondingÂ  with the green school harmony programs. Â  Keywords: Character Education, Green School Harmony, SERU Learning